Susceptibility to Xylella fastidiosa and functional xylem anatomy in Olea europaea: revisiting a tale of plant–pathogen interaction. Issue 4 (21st May 2021) - Petit, Giai; Bleve, Gianluca; Gallo, Antonia; Mita, Giovanni; Montanaro, Giuseppe; Nuzzo, Vitale; Zambonini, Dario; Pitacco, Andrea
Abstract: Xylella fastidiosa is a xylem-limited bacterium causing the Olive Quick Decline Syndrome, which is currently devastating the agricultural landscape of Southern Italy. The bacterium is injected into the xylem vessels of leaf petioles after the penetration of the insect vector's stylet. From here, it is supposed to colonize the xylem vasculature moving against water flow inside conductive vessels. Widespread vessel clogging following the bacterial infection and causing the failure of water transport seemed not to fully supported by the recent empirical xylem anatomical observations in infected olive trees. We tested the hypothesis that the higher susceptibility to the X. fastidiosa 's infection in Cellina di Nardò compared with Leccino is associated to the higher vulnerability to air embolism of its larger vessels. Such hypothesis is motivated by the recognized ability of X. fastidiosa in degrading pit membranes and also because air embolism would possibly provide microenvironmental conditions more favourable to its more efficient aerobic metabolism. We revised the relevant literature on bacterium growth and xylem physiology, and carried out empirical field, mid-summer measurements of xylem anatomy and native embolism in olive cultivars with high (Cellina di Nardò) and low susceptibility (Leccino) to the infection by X. fastidiosa . Both cultivars had similar shoot mass traits and vessel length (~80 cm), but the highly susceptible one had larger vessels and a lower number of vessels supplying a given leaf mass. Native air embolism reduced mean xylem hydraulic conductance by ~58 % (Cellina di Nardò) and ~38 % (Leccino). The higher air-embolism vulnerability of the larger vessels in Cellina di Nardò possibly facilitates the X. fastidiosa 's infection compared to Leccino. Some important characteristics of the vector–pathogen–plant interactions still require deep investigations acknowledging both the pathogen metabolic pathways and the biophysical principles of xylem hydraulics. Abstract : The olive cultivars Cellina di Nardò and Leccino have different susceptibility to the Olive Quick Decline Syndrome caused by the xylem-limited bacterium Xylella fastidiosa . The analysed infected branches of Cellina di Nardò had fewer and larger vessels, and showed higher occurrence of air embolism (higher percent loss of xylem conductance, PLC) in the field compared to those of Leccino. Results would suggest that air embolism in xylem vessels likely plays a key role in predisposing the host plant to a more virulent pathogen attack.